Analysis of the influence of acidification on relevant mechanical parameters of oil shale fracturing. (18th July 2021) - Liu, Kunyan; Nie, Shuaishuai; Zhu, Ying; Zhai, Lianghao; Zhong, Xiuping; Liu, Shuyuan; Chen, Chen
Abstract: Acidification as an effective means of reservoir modification, it is necessary to investigate the influence of acid on the mechanical properties and fracture initiation and extension of oil shale. We conducted acidification test using hydrochloric acid, and performed numerical simulation and multi-factor analysis for hydraulic fracturing. Results show that acidification greatly reduced the elastic modulus and tensile strength by 66.2% and 65.9%, and the void ratio of the oil shale increased from 0.0036 to 0.046. Meanwhile, with increasing acidification time, the fracture morphology extended from oblong to long-narrow and the initiation pressure dropped from 14.03 MPa to 9.39 MPa. We found that the tensile strength of the oil shale was the major factor affecting fracture initiation and extension. Further, an optimal acidification time existed, which was between 48 h and 96 h, wherein acid should be injected again at 48 h to improve the acidification efficiency.